2012
DOI: 10.1159/000335134
|View full text |Cite
|
Sign up to set email alerts
|

Perception versus Reality: The Measuring of Pleural Fluid pH in the United States

Abstract: Background: Pleural fluid pH measured by a blood gas analyzer is the only recommended method of pH measurement to guide management for patients with parapneumonic pleural effusions. Not all hospitals use blood gas analyzers for pleural fluid pH determination and it is unknown if physicians are aware of this problem. Objective: To determine if a discrepancy exists between the modality used for measuring pleural fluid pH and how physicians believe it is measured. Methods: We surveyed pulmonologists randomly acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To date, the most powerful clinical indicator to chest tube drainage is a pleural fluid pH < 7.2, a cut‐off universally agreed among international guidelines. The sample for pH should be collected anaerobically in a heparinized blood gas syringe, as the presence of air can falsely elevate pleural fluid pH, as can delay in measurement . Lidocaine is acidic and falsely depresses fluid pH.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the most powerful clinical indicator to chest tube drainage is a pleural fluid pH < 7.2, a cut‐off universally agreed among international guidelines. The sample for pH should be collected anaerobically in a heparinized blood gas syringe, as the presence of air can falsely elevate pleural fluid pH, as can delay in measurement . Lidocaine is acidic and falsely depresses fluid pH.…”
Section: Diagnosismentioning
confidence: 99%
“…The sample for pH should be collected anaerobically in a heparinised blood gas syringe, as the presence of air can falsely elevate pleural fluid pH, as can delay in measurement. 46 Lidocaine is acidic and falsely depresses fluid pH. Visualisation of frank pus on pleural aspiration is diagnostic of empyema requiring chest tube drainage, and does not require any further confirmatory investigation.…”
Section: Pleural Fluid and Biomarkersmentioning
confidence: 99%
“…Unfortunately, no reliable indicators of the need for surgical intervention have yet been identified. In addition, pH measurements pose some preanalytical challenges (12,13). The results of our study indicated that pleural LDH and glucose levels were increased and decreased, respectively, in patients treated with surgery ( Table 2).…”
Section: Discussionmentioning
confidence: 72%
“…Assessments of pleural guideline adherence have generally focused on the performance of pleural procedures [7,8]. However, at least one other study examined pleural pH measurements in the United States a decade ago, with very similar findings [9].…”
Section: Discussionmentioning
confidence: 98%